Comparison of the effect of stem cell therapy and percutaneous transluminal angioplasty on diabetic foot disease in patients with critical limb ischemia - Dubský, Michal; Jirkovská, Alexandra; Bem, Robert; Fejfarová, Vladimíra; Pagacová, Libuse; Nemcová, Andrea; Sixta, Bedrich; Chlupac, Jaroslav; Peregrin, Jan H; Syková, Eva; Jude, Edward B (Cytotherapy, 2014)
BACKGROUND AIMS: The aim of our study was to compare the effect of autologous stem cell therapy (SCT) and percutaneous transluminal angioplasty (PTA) on diabetic foot disease (DFD) in patients with critical limb ischemia (CLI). METHODS: Thirty-one patients with DFD and CLI treated by autologous stem cells and 30 patients treated by PTA were included in the study; 23 patients with the same inclusion criteria who could not undergo PTA or SCT formed the control group. Amputation-free survival, transcutaneous oxygen pressure (TcPO2) and wound healing were assessed over 12 months. RESULTS: Amputation-free survival after 6 and 12 months was significantly greater in the SCT and PTA groups compared with controls (P = 0.001 and P = 0.0029, respectively) without significant differences between the active treatment groups. Increase in TcPO2 did not differ between SCT and PTA groups until 12 months (both Ps < 0.05 compared with baseline), whereas TcPO2 in the control group did not change over the follow-up period. More healed ulcers were observed up to 12 months in the SCT group compared with the PTA and control groups (84 versus 57.7 versus 44.4 %; P = 0.042). CONCLUSIONS: Our study showed comparable effects of SCT and PTA on CLI, a major amputation rate that was superior to conservative therapy in patients with diabetic foot and an observable effect of SCT on wound healing. Our results support SCT as a potential promising treatment in patients with CLI and diabetic foot.
Keywords: stem cell therapy; angioplastika; Male; percutaneous transluminal angioplasty; Aged; mužské pohlaví; senioři; Diabetic Foot; Peripheral Arterial Disease; onemocnění periferních arterií; transplantace kmenových buněk; autologní štěp; buněčná a tkáňová terapie; lidé; ženské pohlaví; Angioplasty; Cell- and Tissue-Based Therapy; Stem Cell Transplantation; Humans; critical limb ischemia; Autografts; Female; lidé středního věku; Middle Aged; diabetická noha